1996
DOI: 10.1090/s0002-9939-96-03587-3
|View full text |Cite
|
Sign up to set email alerts
|

The real and the symmetric nonnegative inverse eigenvalue problems are different

Abstract: Abstract. We show that there exist real numbers λ 1 , λ 2 , . . . , λn that occur as the eigenvalues of an entry-wise nonnegative n-by-n matrix but do not occur as the eigenvalues of a symmetric nonnegative n-by-n matrix. This solves a problem posed by Boyle and Handelman, Hershkowitz, and others. In the process, recent work by Boyle and Handelman that solves the nonnegative inverse eigenvalue problem by appending 0's to given spectral data is refined. 1.Let M m,n (M m,n (R)) denote the set of all m-by-n compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…In this section we consider the symmetric nonnegative inverse eigenvalue problem (SNIEP). It is well known that the RNIEP and the SNIEP are equivalent for n ≤ 4, while they are different for n ≥ 5 [12]. The first results about symmetric nonnegative realization are due to Fiedler [10].…”
Section: Sniepmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we consider the symmetric nonnegative inverse eigenvalue problem (SNIEP). It is well known that the RNIEP and the SNIEP are equivalent for n ≤ 4, while they are different for n ≥ 5 [12]. The first results about symmetric nonnegative realization are due to Fiedler [10].…”
Section: Sniepmentioning
confidence: 99%
“…If the realizing matrix is required to be symmetric we have the symmetric nonnegative inverse eigenvalue problem (SNIEP), which has been solved for n = 5 with realizing matrices of trace zero by Spector [43]. For n ≤ 4, the RNIEP and the SNIEP are equivalent, while for n ≥ 5, they are different [12]. A number of sufficient conditions for the existence of a symmetric nonnegative matrix with prescribed spectrum have also been obtained (see [33,34,38] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…pdf). Readers also may refer to [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] for some previous results. In some articles, some necessary conditions and sufficient conditions for the three problems above have been given under some small dimension or special cases [7].…”
Section: Problem 3 (Sniep)mentioning
confidence: 99%
“…In [16], Wuwen showed that the RNIEP and the SNIEP are equivalent when n ≤ 4. The fact that the RNIEP and the SNIEP are different for n > 4 was proved by Johnson et al in [3]. The NIEP for 4 × 4 traceless matrices was solved by Reams in [10] and 5 × 5 traceless matrices was solved by Laffey and Meehan in [6].…”
Section: Introductionmentioning
confidence: 99%